2000
DOI: 10.1016/s0735-1097(00)01000-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolving changes in Doppler mitral flow velocity pattern in rats with hypertensive hypertrophy

Abstract: Development of pressure overload LV hypertrophy is associated with evolving changes in MFVP from normal to relaxation abnormality pattern and, in turn, to pseudonormalized to restrictive pattern. Analysis of MFVP may be useful to follow not only functional but also constitutional changes of the myocardium in hypertensive hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 20 publications
9
47
1
Order By: Relevance
“…However, there was no SHR with an E/A below 1.0, which is frequently seen in patients with hypertension and is a criterion for diastolic dysfunction in humans. The normal value of E/A is almost 2.0 in rats (34) .…”
Section: Discussionmentioning
confidence: 82%
“…However, there was no SHR with an E/A below 1.0, which is frequently seen in patients with hypertension and is a criterion for diastolic dysfunction in humans. The normal value of E/A is almost 2.0 in rats (34) .…”
Section: Discussionmentioning
confidence: 82%
“…All subjects in this study had hypertension, and the LV mass index was greater in the DHF patients than in the hypertensive patients without heart failure ( Table 2). Our animal experiments and a recent clinical study have demonstrated that progressive LV hypertrophy is associated with the development of LV fibrosis (27,28), and LV fibrosis plays a crucial role in the enhancement of LV stiffness and the transition from asymptomatic diastolic dysfunction to DHF (27,29,30). LV hypertrophy was not independently associated with the prevalence of DHF (Table 3), and the noninvasive assessment of LV fibrosis is currently difficult.…”
Section: Diastolic Dysfunction and Dhfmentioning
confidence: 74%
“…Peak early diastolic filling velocity (E velocity), peak filling velocity at atrial contraction (A velocity) and their ratio (E/A ratio) were measured for consecutive five cardiac cycles. 22 …”
Section: Animal Preparationmentioning
confidence: 99%